MOLECULAR IDENTIFICATION OF SHOREA JOHORENSIS IN KETAMBE RESEARCH STATION, GUNUNG LEUSER NATIONAL PARK - Nir Fathiya; Essy Harnelly; Zairin Thomy; Iqbar Iqbar (Universitas Syiah Kuala, 2018)
Shorea johorensis is one of the red meranti plants in Ketambe Research Station, Gunung Leuser National Park, Aceh Tenggara. Currently, Shorea johorensis also is well known as a major source of valuable commercial timber. This research aimed to analyze the phylogenetic of Shorea johorensis based on chloroplast and nuclear DNA in Ketambe Research Station so that it can be known the relationship of Shorea johorensis with other species Dipterocarpaceae in GenBank database. The research was conducted from July 2015 to August 2016 in Ketambe Research Station and Forestry and Forest Genetics Laboratory of Molecular, Bogor Agricultural University. The method used quadrat sampling technique with purposive sampling and experimental laboratory that consisted of DNA extraction, PCR, electrophoresis, and sequencing. The data analysis was done using BioEdit, MEGA6, and BLAST. The results showed that the phylogenetic tree of Shorea johorensis based on the rbcL and matK showed that Shorea johorensis was closely related with some species Hopea; but the phylogenetic tree based on psbA-trnH, 5.8S rRNA, ITS2, and 28S rRNA showed that Shorea johorensis was closely related with Shorea robusta.Keywords: Chloroplast dna, Ketambe Research Station,Nuclear DNA, Shorea johorensis